2020
DOI: 10.1097/jom.0000000000002080
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Small Business Safety and Health Climates During COVID-19

Abstract: Objective: This study examines employee perceptions of safety and health climates for well-being during the COVID-19 pandemic in a sample of small businesses. Methods: We evaluated changes to employees’ work and home life resulting from COVID-19 and perceptions of safety and health climates. Cross-sectional relationships were assessed using multivariable linear regression models for a sample of 491 employees from 30 small businesses in Colorado in May 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…How an organisation responds to the COVID-19 pandemic can have profound effects on the safety, health, and well-being of its employees [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…How an organisation responds to the COVID-19 pandemic can have profound effects on the safety, health, and well-being of its employees [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include a commitment to the physical and emotional health, wellbeing, and safety of workers; supportive and flexible supervisors and leadership; frequent and honest communication and dialogue; flexible work provisions; encouragement and support of worker engagement in both identifying and solving problems; and enhanced organisational benefits (eg, financial assistance to establish ergonomic remote offices, childcare assistance, sick leave policies, and caretaker leave policies). 73 , 74 , 75 , 76 …”
Section: Applying a Public Health Perspective After The Pandemicmentioning
confidence: 99%
“…Schwatka et al [ 33 ] found that organizational safety and the health climate were positively correlated with the healthy behaviors of workers in small businesses. During the COVID-19 pandemic, although no study has directly examined the relationship between the institutional climate and preventive behaviors of COVID-19, several recent studies have provided insight into the role of institutional factors that protect against the negative effects of the COVID-19 pandemic and promote precautionary actions to minimize risk while sustaining psychological wellbeing [ 34 , 35 ]. In particular, Tausen et al [ 36 ] reported that the response and support of universities combating COVID-19 increased the subjective well-being of Asian students at a predominantly white university during the COVID-19 crisis in the US.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%